Low complexity MIMO-OFDM channel estimation based on space time block training sequence - DONG Liang; CAO Xiu-ying; BI Guang-guo (Tongxin xuebao)
In order to improve the performance of MIMO-OFDM channel estimation,the connection between MMSE channel estimator and subspace projecting was analyzed in the context of space time block training sequence firstly.Then the LS channel estimator obtained simply by space time block training sequence was projected to the signal subspace to get an estimator that was efficient but of low complexity.To further improve the estimation performance,the multipath delay was estimated by FFT,and then a more accurate channel response signal space was obtained,so the performance of subspace projecting was also improved.The efficiency of the algorithms presented is proved by computer simulations.